PERANCANGAN SISTEM PAKAR DALAM MENDIAGNOSA KERUSAKAN CCTV BERBASIS WEB MENGGUNAKAN METODE FORWARD CHAINING (STUDI KASUS: PT.MNC PICTURES) - Andica Dinata; Asrul Sani (STMIK Widuri Jakarta, 2023)
The use of Closed Circuit Television (CCTV) has almost become a common necessity in the current era, especially for security, where it is to record an incident 24 hours a day which can be immediately broadcast or stored as evidence if one day it is needed. Closed Circuit Television or better known as CCTV is equipment that functions to record events in real time in a room. The research objective is to build a web-based expert system that is able to diagnose damage to CCTV and implement the forward chaining method. Data collection methods are observation, interviews and literature study. Meanwhile, the research method used is forward chaining. The result is that an expert system can be built on a web basis and is able to diagnose damage to CCTV and also the forward chaining method can be implemented to overcome the uncertainty of the expert system diagnosis results.